The Whodunit Challenge: Mobilizing the Crowd in India - Vaish, Rajan; Cutrell, Edward; Thies, William; Thies, Bill; Cutrell, Ed (Springer, 2015)
While there has been a surge of interest in mobilizing the crowd to solve large-scale time-critical challenges, to date such work has focused on highincome countries and Internet-based solutions. In developing countries, approaches for crowd mobilization are often broader and more diverse, utilizing not only the Internet but also face-to-face and mobile communications. In this paper, we describe the Whodunit Challenge, the first social mobilization contest to be launched in India. The contest enabled participation via basic mobile phones and required rapid formation of large teams in order to solve a fictional mystery case. The challenge encompassed 7,700 participants in a single day and was won by a university team in about 5 hours. To understand teams’ strategies and experiences, we conducted 84 phone interviews. While the Internet was an important tool for most teams, in contrast to prior challenges we also found heavy reliance on personal networks and offline communication channels. We synthesize these findings and offer recommendations for future crowd mobilization challenges targeting low-income environments in developing countries.